Analysis Usability System Web E-Office at PT Pelabuhan Indonesia II Using Heuristic Evaluation (Case Study of PT Pelabuhan Palembang) - Selia Tasya; Fatmasari Fatmasari (Budapest International Research and Critics University, 2022)
PT Pelabuhan Indonesia II (Persero) is a State-Owned Enterprise engaged in logistics in port management and development. At PT Pelabuhan Indonesia II Palembang branch there is an E-OFFICE web that can be accessed through the website. The E-OFFICE is a website system that can only be accessed by employees and is used to facilitate correspondence activities within PT Pelabuhan Indonesia II Palembang branch. The purpose of this study was to determine the level usability system of the E-OFFICE web, whether it was easy to learn, efficient, when users interacted it was easy to remember procedures/steps without making many mistakes, and finally whether users felt comfortable operating the website. This study uses a heuristic evaluation method that contains ten variables, namely Visibility of system status, Match between system and the real world, User control and freedom, Consistency and standard, Error prevention, Recognition rather than recall, Flexibility and efficiency of use, Aesthetic and minimalist, Help users recognize, Diagnose and recover from errors,Help and documentation. The population of this research is employees, using questionnaire data collection techniques and interviews with samples. This research can be used as input for development in increasing the usability value.